2008
DOI: 10.1007/s11426-007-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of graded polyurethane elastomer by FTIR

Abstract: Polyurethane elastomers with graded structure were prepared in the graded temperature field. The samples were characterized by FTIR technology. The results show that the degree of microphase separation in the samples decreases with the decrease of the curing temperature. As far as the molar ratio of NH 2 and NCO is concerned, the sample exhibits better graded morphology when the ratio is 0.95. The transparence of the samples prepared also changes gradually, increasing along the direction, in which temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Curing the EPU/Bifenthrin® blends followed the same procedure as for the unblended EPU described earlier. Previous work8 has shown that in a sample containing nominally 4 wt % Bifenthrin®, ∼ 10% of the Bifenthrin® is lost during the degassing and curing procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curing the EPU/Bifenthrin® blends followed the same procedure as for the unblended EPU described earlier. Previous work8 has shown that in a sample containing nominally 4 wt % Bifenthrin®, ∼ 10% of the Bifenthrin® is lost during the degassing and curing procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Bifenthrin® is comprised of aromatic and nonaromatic groups, Figure 1, and thus there exists the possibility of interaction between the aromatic groups of the active and the isocyanate group of the EPU, in this case toluene di‐isocyanate (TDI). Although FTIR has been used to analyze EPU8 and pyrethroids9 separately, their interactions have not been explored. The Bifenthrin® molecule also contains fluorine and this element presents an excellent marker for X‐ray photoelectron spectroscopy (XPS) analysis of the distribution of the active within the EPU and its presence on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that “winning strategy in term of more absorbed energy with a low transmitted force could consist of placing the ‘hardest' layer as the first impacted layer and the ‘weakest' layer in contact with the protected structure to reduce the transmitted force.” This effect is strong only under high impact speed. Also, graded PUs might have potential for antierosion coatings . However, there are not enough studies about their application in coatings.…”
Section: Polymer Structuresmentioning
confidence: 99%
“…Also, graded PUs might have potential for antierosion coatings. 56 However, there are not enough studies about their application in coatings.…”
Section: Impact-absorbing Coatingsmentioning
confidence: 99%
“…Among them, polyurethanes are an important and versatile class of polymers that have found widespread applications in biomedical field [10]. Generally, polyurethane based materials are widely used in coatings [11], paints [12], foams [13], elastomers [14][15][16], adhesives [17] and medical devices [18][19][20]. Thereby, polyurethane based materials have been the subject of several studies aimed to design advanced materials with high performances [21][22][23].…”
Section: Introductionmentioning
confidence: 99%